Strategic Financial Fluency: Catalyst For Growth In Micro, Small, And Medium Enterprises - Eri Kusnanto; Ngadi Permana; Benardi Benardi (Proceeding of The International Conference on Business and Economics, 2023)
This qualitative research aims to explore the role of Strategic Financial Fluency (SFF) as a catalyst for growth in Micro, Small, and Medium Enterprises (MSMEs). The study employs a multi-method approach integrating literature review, case studies, and expert interviews to construct a comprehensive understanding of SFF and its impact on MSMEs' growth trajectories. Sampling techniques involve purposive sampling of MSMEs representing diverse industries and geographical locations to ensure comprehensive data collection. Data analysis employs thematic analysis, focusing on identifying patterns and themes related to SFF adoption, utilization, and its influence on business growth. The findings reveal that MSMEs equipped with Strategic Financial Fluency demonstrate higher adaptability, resilience, and growth potential. Moreover, SFF facilitates informed decision-making, efficient resource allocation, and strategic planning, thus fostering sustainable growth in MSMEs. This research contributes to the existing literature by highlighting the pivotal role of financial literacy and strategic financial management in enhancing the competitiveness and growth prospects of MSMEs in a dynamic business environment.